How Does Occupational Licensing Affect Entry into the Medical Field? An Examination of EMTs - Aaron Yelowitz; Samuel J. Ingram (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic has led to temporary suspensions of many occupational licensing laws, especially for health care professionals, in an effort to manage surges in health care demand. The crisis highlights more general concerns about occupational licensing laws, yet convincing empirical evidence on the degree to which such laws have inhibited entry into health care professions is scarce because most studies must rely on cross-sectional variation to identify such effects. In this study, we indirectly examine how occupational licensing affects the choice to become an Emergency Medical Technician (EMT) by exploiting the demand-side shock from the Affordable Care Act (ACA). Although demand-side shocks should increase the likelihood of becoming an EMT relative to other similar non-medical professions, this effect should be moderated in states with higher barriers to entry. Using a large number of individuals from the American Community Survey (ACS) who work as either EMTs or in a similar non-medical field (protective services), we find suggestive evidence that while the demand-side shock from the ACA increased the likelihood of being an EMT, this effect was substantially moderated by more stringent occupational licensing laws. Although the effect for the full sample is marginally significant, the estimated effects are substantially larger for individuals under age 40, who are presumably more flexible in choosing a career path. Evaluated at the average number of days to complete EMT training and the pre-treatment uninsured rate, the implied effects for young individuals in the most careful specification suggests virtually complete offset; the ACA demand-side shock would increase entry by 18 percentage points, while occupational licensing restrictions reduce entry by a similar magnitude.
Keywords: J44; K31; I13; 330; Occupational Licensing; Occupational Choice; Emergency Medical Technicians; Emergency Services